Network relationship between cognitive function and quality of life in community-dwelling older adults: an observational study from Beijing - Yitian Ye; Yichun Zhang; Jiaju Ren; Yanbo Zhu; Yanbo Zhu (Frontiers in Public Health, 2025)
ObjectiveThis observational study aims to comprehensively explore the network relationship and mechanism of action between cognitive function and quality of life among community-dwelling older adults aged 60 and above in Beijing.MethodsThe research encompassed a cohort of 323 older adults individuals residing in the community in Beijing. Data were collected from January to July 2024 using convenience sampling. Cognitive function was evaluated using the Chinese adaptation of the Montreal Cognitive Assessment (MoCA), while quality of life was assessed through the Medical Outcomes Study 36-Item Short-Form Health Survey version 2 (SF-36v2). Cognitive assessment involved seven dimensions, namely visuospatial/executive function, naming, attention, language, abstraction, delayed recall, and orientation. Concurrently, quality of life was assessed across eight dimensions: physical functioning, role physical, bodily pain, general health, vitality, social functioning, role emotional, and mental health. Network analysis graphs were developed to investigate the interrelationships among variables, identify central nodes, and evaluate stability.ResultsIn the network, the dimensions of social functioning, role-physical, physical functioning, general health, vitality, orientation, and language showed high centrality strength. The dimensions of physical functioning, role-physical, language, and orientation exhibited strong closeness and betweenness. There were strong associations between role-physical and social functioning, physical functioning and role-physical, and vitality and mental health. The centrality stability coefficients for strength, closeness, and betweenness were 0.672, 0.672, and 0.285, respectively.ConclusionThe network structure was stable, indicating that dimensions such as social functioning, role-physical, and physical functioning play pivotal roles influencing cognitive function in community-dwelling older adults. Orientation and language were the most representative dimensions of cognitive function and may serve as important targets for interventions aimed at improving cognitive function and subsequently enhancing QoL. These findings provide practical guidance for community health interventions. Future research should explore causal relationships and develop scalable strategies to support aging populations.